Microsoft Azure Data Engineer Associate (DP-203) Cert Prep by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2024)
Review the core concepts and technical skills required to tackle the Microsoft Azure Data Engineer Associate (DP-203) certification exam.